2012
DOI: 10.4103/2230-973x.100036
|View full text |Cite
|
Sign up to set email alerts
|

Stimuli sensitive hydrogels for ophthalmic drug delivery: A review

Abstract: Amongst the various routes of drug delivery, the field of ocular drug delivery is one of the most interesting and challenging endeavors facing the pharmaceutical scientist for past 10-20 years. As an isolated organ, eye is very difficult to study from a drug delivery point of view. Despite this limitation, improvements have been made with the objective of maintaining the drug in the biophase for an extended period. A major problem in ocular therapeutics is the attainment of an optimal drug concentration at the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
57
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(63 citation statements)
references
References 33 publications
0
57
0
Order By: Relevance
“…Gellan gum (GG) [6][7][8] has been proposed to increase ocular bioavailability in the ophthalmic formulation because of its reticular properties due to eye tears divalent cations and calcium. Gellan gum is a high molecular weight and linear anionic heteropolysaccharide produced by aerobically bacteria Aeromonas (Pseudomonas) elodea, which is composed of a tetrasaccharide repeating unit of glucose, glucuronic acid and rhamnose [9,7]. Carrageenan's are another group of natural polymers which can be proposed for use in the ophthalmic formulation [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Gellan gum (GG) [6][7][8] has been proposed to increase ocular bioavailability in the ophthalmic formulation because of its reticular properties due to eye tears divalent cations and calcium. Gellan gum is a high molecular weight and linear anionic heteropolysaccharide produced by aerobically bacteria Aeromonas (Pseudomonas) elodea, which is composed of a tetrasaccharide repeating unit of glucose, glucuronic acid and rhamnose [9,7]. Carrageenan's are another group of natural polymers which can be proposed for use in the ophthalmic formulation [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…These external conditions can be used as triggers to more specifically control drug release in a 'smart' manner. These bioresponsiveness switches turn drug release on and off according to spatial or temporal requirements of the drug, thus reducing the frequency of drug administration and the side effects due to off-targeting and undesired body distribution [44,45].…”
Section: Hydrogelsmentioning
confidence: 99%
“…However, the development of pH-sensitive gels must take into account the delicate environment of the eye. The formulation must have a buffer capacity that can form a gel when placed into the eye but not cause damage to the eye (Kushwaha et al, 2012).…”
Section: Ph-sensitive Hydrogel Systemsmentioning
confidence: 99%
“…Although many of the polymers used in pH-sensitive hydrogels are synthetic polymers, such as carbopol [polyacrylic acid (PAA)] and polyethylene glycol, natural biopolymers are also used in the formulations to give them more favorable characteristics (Kushwaha et al, 2012;Wu et al, 2013). For example, in a study performed by Kumar and Himmelstein (1995), it was shown that, although PAA is able to change from a low viscosity liquid when in an acidic solution to a gel at a higher pH, the amount of PAA needed for this to occur was too high.…”
Section: Ph-sensitive Hydrogel Systemsmentioning
confidence: 99%